Accessory phase perspectives for ore-forming processes and magmatic sulphide exploration in the Labrador Trough, northern Québec, Canada - Smith, William Daniel; Maier, Wolfgang D.; Andersen, Jens C.O.; Muir, Duncan D.; Mansur, Eduardo; Bliss, Ian (Canadian Journal of Earth Sciences, 2022)
The compositions of resistant indicator minerals are diagnostic of their original host environment. They may be used to fingerprint different types of mineral deposit as well as vector towards them. We have characterised the composition of apatite and Fe-Ti oxides in variably-mineralised mafic-ultramafic rock units of the Montagnais Sill Complex in the Labrador Trough to assess their suitability for vectoring magmatic sulphide occurrences. Two broad types of apatite were identified: (i) fluoro- to hydroxy-apatite (Cl/[Cl+F] < 0.2); and (ii) chloro- to hydroxy apatite (Cl/[Cl+F] > 0.5). The former reflects variable degrees of degassing and Cl-loss during Rayleigh fractionation and is not indicative of Ni-Cu-mineralisation or host rock. The latter exists only in sulphidic olivine cumulate units and thus, may be used to vector similar rock types in the Labrador Trough. Ilmenite is the dominant oxide, except for the upper parts of differentiated gabbroic sills in which titanomagnetite is dominant. Magnetite occurs only as a secondary phase in serpentinised olivine cumulates and is not discriminative for magmatic sulphides. Ilmenite and titanomagnetite in the sulphidic olivine-bearing units have characteristically high Mg (~ 1,000-10,000 ppm), Cr (~ 100-1,000 ppm), Ni (~ 10-1,000 ppm), and Cu (~ 1-10,000 ppm) concentrations relative to those from other rock units. Their composition is consistent with Fe-Ti oxides derived from evolved sulphide melts in ultramafic-hosted Ni-Cu-(PGE) sulphide deposits and thus may be used to vector towards similar magmatic sulphide occurrences in the Labrador Trough.